Public Service Innovation through Smart Tourism Policy at the Banyumas Regency Tourism Office - Isty Mustikaningtyas W; Azriah, Thahrina (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2026)
The implementation of digitalization in the tourism sector has become a crucial agenda for local governments to optimize regional revenue and accelerate service delivery. This study aims to analyze public service innovation through the smart tourism policy implemented by the Banyumas Regency Youth, Sports, Culture, and Tourism Office (Dinporabudpar). The research method used is descriptive qualitative, with data collection techniques through interviews with agency officials, destination managers, and tourists, as well as field observation and documentation. The research findings indicate that the Smart Tourism policy in Banyumas Regency, particularly through the implementation of an integrated e-ticketing system and digitalized promotions, has succeeded in increasing bureaucratic efficiency and transparency in the management of local revenue. However, the effectiveness of this innovation is still hampered by the limited digital literacy capacity of some human resources in the field and infrastructure network constraints in mountainous tourism areas. The implications of this study emphasize the importance for local governments to focus not only on providing technological infrastructure, but also on strengthening regulatory capacity and providing ongoing human resource assistance so that digital-based public service innovations can run inclusively and optimally.